Best nursing practices in type I Urine Collection: Pre-analytical safety and technique standardization (Research, Society and Development, 2025)
Type I urine collection is a widely used clinical procedure for investigating urinary tract infections, metabolic disorders, renal function, and systemic conditions. However, the pre-analytical phase remains the most critical step in ensuring reliable laboratory results, as errors related to inadequate patient guidance, improper technique, and incorrect sample transport can significantly compromise clinical interpretation. This article presents a narrative literature review on best nursing practices in Type I urine collection, emphasizing the importance of technique standardization, patient education, and the adoption of pre-analytical safety measures. The review discusses the purpose of the exam, key laboratory parameters, proper collection techniques for adults and children, common errors and their consequences, prevention strategies, biosafety considerations, and recommendations for proper sample transport. Findings demonstrate that nurses play a central role in performing and supervising the procedure safely, acting as educational and quality-assurance agents in the pre-analytical phase. The literature shows that implementing standardized protocols, checklists, periodic training, and internal audits substantially reduces contamination rates and increases the reliability of laboratory results. It is concluded that strengthening nursing practices, combined with institutional investment in infrastructure and continuing education, is essential to ensure diagnostic accuracy and promote patient safety in healthcare services.